Pemanfaatan Desain Komunikasi Visual dalam Mendorong Perekonomian Kreatif di SMK Techno Media Tangerang Selatan - Sutihat, Aat; Budiantini, Alya; Jelanti, Desi (Jurnal PKM Manajemen Bisnis, 2025)
The development of the creative economy in Indonesia relies heavily on innovation and the ability to utilize digital tools, particularly in the field of Visual Communication Design (VCD). Recognizing the need to empower students with practical design knowledge, a community service activity was conducted at SMK Techno Media Tangerang Selatan. The aim of this PKM (Pengabdian kepada Masyarakat) was to introduce and apply Visual Communication Design as a strategy to support the students’ entrepreneurial skills and foster the growth of the creative economy. The activity took place on April 16, 2025, involving three lecturers and four students from the Accounting Study Program at Universitas Pamulang. A total of 30 students from SMK Techno Media participated in the program. The methods used included presentations, hands-on practice, group discussions, and Q&A sessions. Materials covered included design principles, branding, and the use of digital design software. As a result, students demonstrated increased understanding of visual branding and showed enthusiasm in applying design to promote their products or services. This PKM initiative highlighted the importance of integrating visual literacy into vocational education to enhance students’ creative potential and economic empowerment.